Peningkatan Hasil Belajar Siswa Kelas 5 SD Dalam Menggunakan Model Problem Based Learning(PBL) - Umi Choiriyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The research is motivated by the lack of maximum student learning outcomes at SDN 5 Bondo. There are 15 student from 18 student who score bellow KKM below 70 with an average score of 56,5. There were 15 students from 18 students who got grades below the KKM which were under 70 with an average score of 56.5. The existence of these problems, then held an effort to improve learning so that student learning outcomes can improve through classroom action research. The type of research that will be used is Classroom Action Research (CAR) which is carried out in two cycles. Technique of collecting data using observation and test result of learning Result of research have increased percentage of learning result and student learning activity reaching KKM at cycle I and II increase. Teachers should use Problem Based Learning (PBL) learning models to improve student learning outcomes. Improve student learning outcomes.